Sekuritisasi China Fine Dust oleh Pemerintah Korea Selatan terhadap Tiongkok - Eryolanda Putri Nabila (Andalas Institute of International Studies, 2021)
China Fine Dust issue has emerged in 2013 and increase in 2014 so that South Korea suffered from the impact. Meanwhile, China as a contributor of the haze refuses to take responsibility for tackling this issue, so that South Korea must securitize. This study aims to describe the process of securitization of China Fine Dust issue carried out by South Korea to China by using the concept of securitization by Barry Buzan as an analytical framework. The research method used is a qualitative method with a descriptive approach. The data used in this research was collected through literature study. The securitization process carried out by the South Korean Government against China began with South Korea carrying out a scientific agenda to identify a threat with China's initial involvement of 48%. Then political agenda, which are three points; influencing the public to gain support, forming a domestic emergency policy, holding a bilateral meeting to convince China to work together because domestic actions are not enough yet. The continuation of political management shows that the agenda of securitization carried out by South Korea made China accept the issue as a threat and agreed to cooperate in tackling the haze issue by releasing several projects.